Managing Change: A Case of National Bank - Mainrai, Girish (Prabandhan: Indian Journal of Management, 2019)
National Bank, a public sector bank which is in its 65th year of existence, got its first MD & CEO from the private sector in the form of Mr. Bandyopadhyay as a part of policy changes introduced by the regulator. The new MD undertook a slew of measures under Project 'Transformation,' which included improving customer service, introduction of marketing, and revamping human resource policies. These measures intended for improving the position of the bank led to widespread dissatisfaction among the staff. The top management is now contemplating ways to reduce this dissatisfaction and make the project successful.